1988
DOI: 10.1080/10934528809375436
|View full text |Cite
|
Sign up to set email alerts
|

Organic cation effects on the sorption of metals and neutral organic compounds on aquifer material

Abstract: Sorption of ethylhexadecyldimethyl ammonium (EHDDMA+), a large organic cation, and three neutral organic compounds (NOC's) on two low organic carbon aquifer materials was studied using a soil batch equilibration technique. EHDDMA+ competed effectively with metals for exchange sites and EHDDMA+ sorption was accompanied by an equimolar charge desorption of metals. NOC's sorption on the aquifer materials was low (K 0.22) which was consistent with the sorbent's low organic carbon content. However, EHDDMA+ sorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

1994
1994
2003
2003

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…In fact, the surface area of the K-soil is more than 20 % of that of activated carbon (Nakhla, 1989) which is a conventional manufactured adsorber. Since, previous research (Chion et al, 1983;Garbarini et al, 1986;Boyd et al, 1988;Lee et al, 1989;Bouchard et al, 1988;Smith et al, 1990;Smith and Faffe, 1991 and Haus and Uchvin) established the effect of surfactant treatment on the sorption capacity of the clay, X-ray diffraction (XRD) tests were conducted, mainly, to investigate the existence of clay in the K-soil. The results of the XRD analysis showed that the K-soil contained 68% quartz, 24% muscovite (clay), and 8% hedenbergite.…”
Section: Soil Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the surface area of the K-soil is more than 20 % of that of activated carbon (Nakhla, 1989) which is a conventional manufactured adsorber. Since, previous research (Chion et al, 1983;Garbarini et al, 1986;Boyd et al, 1988;Lee et al, 1989;Bouchard et al, 1988;Smith et al, 1990;Smith and Faffe, 1991 and Haus and Uchvin) established the effect of surfactant treatment on the sorption capacity of the clay, X-ray diffraction (XRD) tests were conducted, mainly, to investigate the existence of clay in the K-soil. The results of the XRD analysis showed that the K-soil contained 68% quartz, 24% muscovite (clay), and 8% hedenbergite.…”
Section: Soil Characterizationmentioning
confidence: 99%
“…Boyd et al (1988) and Lee et al (1989) have used cationic surfactants to modify soils and increase their retardation of nonpolar organics. Bouchard et al (1988) demonstrated that ethyl hexadecyl dimethyl ammonium (EHDDMA) increased the toluene sorption capacity of aquifer material from Lula, Oklahoma by two orders of magnitude. Most earlier works (Boyd et al, 1988;Lee et al, 1989;Smith et al, 1990 andFaffe, 1991) have focused on nonpolar organic contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the adsorption on soil organic matter of acid and dimethyl amine forms of herbicides, which form anionic species in aqueous environment, is minimal (Best et al 1972). Treatment of soils with the cationic surfactant increases their adsorption capacity for anionic organic compounds (Bouchard et al 1988;Lee et al 1989).…”
mentioning
confidence: 99%
“…The retention and mobility of charged organic compounds in soil depend on the ion exchange capacity (Bouchard et al 1988). Strong adsorption of cationic organic chemicals occurs on soil organic matter (Best et al 1972;Grover and Smith 1974).…”
mentioning
confidence: 99%
“…Vários trabalhos onde foi estudada a sorção durante o transporte de pesticidas destacam a difusão na matéria orgânica como causa do não-equilíbrio verificado no transporte (Bouchard et al, 1988;Lee et al, 2002;Gonzalez & Ukrainczyk, 1999 . Garmerdinger et al (1991) observaram esta relação inversa estudando o transporte de herbicidas do grupo das triazinas e atribuíram o não-equilíbrio no transporte de triazinas à difusão na matéria orgânica do solo.…”
Section: Mecanismosunclassified